Spatial and temporal patterns and their influence on fish community at Itupararanga Reservoir, Brazil - Smith, Welber Senteio; Petrere Jr., Miguel [UNESP] (My University, 2008)
The Itupararanga Reservoir is located at the Sorocaba River Basin, São Paulo State, Brazil. Five cities use the waters of this reservoir for human consumption. Despite this intensive use of the water resource, no study has been undertaken on the ichthyofauna of this reservoir. Collections were performed in nine sampling stations, where each three were located in the riverine, transitional and lacustrine zones. Fish specimens were collected using eight monofilament gillnets of 10 m length each, with varied mesh sizes, in the rainy and dry seasons, which corresponded to our spatial scale of analysis. Overall, 14 species of fish were identified, with the highest contribution from Characidae and Curimatidae. The most abundant species were: the lambari, Astyanax fasciatus, the saguiru, Cyphocharax modestus, the lambari bocarra, Oligosarcus paranaensis, and the mandi, Iheringichthys labrosus. Diversity tended to be higher during the dry season, although the difference was not statistically significant. Cluster analysis identified four season sampling groups differentiated by within-season distribution of species. Mantel's test showed that this distribution was little affected by environ- mental factors, suggesting that biotic factors were more important in determining the species distribution within the reservoir.
Keywords: Ichtyofauna; Itupararanga Reservoir; Sorocaba river; Species diversity; Species richness; Structure community